2008
DOI: 10.1007/s00299-008-0627-5
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid-induced changes to growth and phenolic metabolism in Matricaria chamomilla plants

Abstract: The influence of salicylic acid (SA) doses of 50 and 250 microM, for a period of up to 7 days, on selected physiological aspects and the phenolic metabolism of Matricaria chamomilla plants was studied. SA exhibited both growth-promoting (50 microM) and growth-inhibiting (250 microM) properties, the latter being correlated with decrease of chlorophylls, water content and soluble proteins. In terms of phenolic metabolism, it seems that the higher SA dose has a toxic effect, based on the sharp increase in phenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(80 citation statements)
references
References 34 publications
8
66
0
3
Order By: Relevance
“…Higher concentration of FA (1000 ppm) inhibited seedling growth which was reflected by decrease in shoot length and biomass of roots and shoots (Table 1). These results are in harmony with Kovacik et al (2009) who explained that high doses of SA led to sharp increase in soluble phenolics and lignin accumulation and thereby inhibition of growth. Based upon seedling growth, 100 ppm of FA was chosen for studying the effect of FA pre-treatment on antioxidant defense system.…”
Section: Discussionsupporting
confidence: 74%
“…Higher concentration of FA (1000 ppm) inhibited seedling growth which was reflected by decrease in shoot length and biomass of roots and shoots (Table 1). These results are in harmony with Kovacik et al (2009) who explained that high doses of SA led to sharp increase in soluble phenolics and lignin accumulation and thereby inhibition of growth. Based upon seedling growth, 100 ppm of FA was chosen for studying the effect of FA pre-treatment on antioxidant defense system.…”
Section: Discussionsupporting
confidence: 74%
“…The inhibition of chlorophyll biosynthesis under high-temperature regimes results from a destruction of numerous enzymes involved in the mechanism of chlorophyll biosynthesis [47]. As stated in the Introduction, the influence of exogenous salicylic acid depends on various factors, including the concentration of salicylic acid, the developmental phase, the species and the method of application [1]. The lack of effect of the salicylic acid on the chlorophyll content may be due to the high intensity of heat stress so that severe heat stress impairs plastid and chlorophyll structures and decreases the contributing effect of exogenous salicylic acid.…”
Section: Total Chlorophyll Contentmentioning
confidence: 99%
“…Salicylic acid (SA) is a well-known endogenous plant signal molecule involved in biochemical pathways, disease resistance and many plant responses [1]. On the other hand, SA is a signaling molecule that regulates plant responses to heat stress and disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Umbelliferone (7-hydroxycoumarin) was identified as a stress metabolite (Repčák et al 2001a). Previous results of time-dependent study showed that accumulation of coumarin-realated compounds in hydroponically cultivated chamomile was affected by exogenous SA application Kováčik et al 2009). Therefore the aim of this paper was to study the effect of foliar spray application of SA on the accumulation of the main coumarin-related compounds, polyacetylenes and chlorogenic acid in dose-dependent manner in the leaf rosettes of chamomile (Matricaria chamomilla L.).…”
Section: Introductionmentioning
confidence: 99%